Ações de produção do conhecimento e transferência de tecnologia relacionadas com veículos elétricos: estudo no campus Ponta Grossa da Universidade Tecnológica Federal do Paraná - Tramontin, Anselmo Gomes (2022)
The objective of the study was to characterize the level of KTT actions related to electric vehicles carried out on the Ponta Grossa campus by isolated investigators and research groups. For this, a systematic review of the literature was carried out, with which it was possible to identify the actions to be carried out in the definition of the KTT model to understand the TT actions carried out on the Ponta Grossa campus. The exciting results that KTT models employed in institutions are efficient and can generate facilitation between industry and university. Another point of fundamental importance is the institution's interest in promoting these projects, since there is local sponsorship and incentives, even though the activities are quantitatively scarce. In view of this, it is clear that the existing projects are viable and important, as well as the ways of structuring the KT are satisfactory for serving the industry and the interests of the Ponta Grossa Campus. However, the study corroborates to offer a diagnosis that it is necessary to increase this amount, as well as to make greater investments in the sector.